Mengembangkan Studi Islam Sebagai Basis Keilmuan Pendidikan Islam - Jajat Darojat (Misykah : Jurnal Pemikiran dan Studi Islam, 2021)
Islamic scientific studies are increasingly interesting to discuss. There are many things about the development of Islamic scholarship that can be studied and developed. Islamic studies in all aspects can provide color to the study of science, including in the context of Islamic education. Islam as a complex value system has a legal basis and source that is original texs. But not a few among the Muslim community still view Islam narrowly, namely as a religion that has limits on matters that are normative, formalistic and symbolic. The perspective that cornered Islam to a religion that is rigid to the context and civilization of society. This is necessary for the development of Islamic studies which have relevance to various fields of scientific disciplines, including Islamic education. The theory of Islamic studies about education which is described through a conceptual structure is placed as a subject that understands reality. So Islamic Studies is a study that can provide a solid foundation and a strong foundation in developing Islamic education. Abstrak Studi keilmuan Islam semakin hari semakin menarik untuk didiskusikan. Banyak hal perkembangan keilmuan Islam yang berkembang dan dapat dikaji. Studi keIslaman dalam segala aspek bisa memberikan warna bagi kajian ilmu termasuk dalam konteks pendidikan Islam. Islam sebagai sistem nilai yang kompleks memiliki dasar dan sumber hukum yang bersifat original texs. Namun tidak sedikit dikalangan masyarakat muslim masih memandang Islam secara sempit, yakni sebagai agama yang memiliki batas pada hal-hal yang bersifat normatif, formalistis dan simbolis. Cara pandang yang menyudutkan Islam pada agama yang kaku terhadap konteks dan peradaban masyarakat. Hal inilah perlu adanya pengembangan Studi Islam yang memiliki relevansi terhadap berbagai bidang disiplin keilmuan, tidak terkecuali pendidikan Islam. Teori Studi Islam tentang pendidikan yang tergambarkan melalui struktur konseptual diletakkan sebagai subyek yang memahami realitas. Maka Studi Islam adalah kajian yang dapat memberikan fondasi yang kokoh dan landasan yang kuat dalam mengembangkan pendidikan Islam.